2019
DOI: 10.1002/app.48850
|View full text |Cite
|
Sign up to set email alerts
|

Simple and feasible strategy to fabricate microcellular poly(butylene succinate) foams by chain extension and isothermal crystallization induction

Abstract: In this article, a facile and efficient isothermal crystallization induction method was proposed to fabricate microcellular poly(butylene succinate) (PBS) foams with supercritical CO2. The good regularity of PE chain segments and high reactive epoxy groups in ethylene‐glycidyl methacrylate copolymer (PE‐g‐GMA) serving as a chain extender were employed to improve the crystallization behaviors, viscoelasticity, and foaming behaviors of PBS through chain extension reaction. The effect of PE‐g‐GMA content on the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 67 publications
0
14
0
Order By: Relevance
“…In Figure 4 a, it can be observed that at about −55 °C curvilinear steps were caused by the glass transition of the composites and the curvilinear steps became less distinct with the gradual addition of EUG. This is mainly because at the glass transition temperature, a large number of EUG crystals still existed in the composites owing to the high melting point of the EUG crystalline region, which hindered the molecular chain movement of the composites [ 29 , 30 ]. Besides, it can be found in Table 2 and Figure 4 that with the increase of EUG content, the crystallinity of various MPU/EUG composites gradually increased and their crystallization melting peak gradual appeared and became more and more obvious at about 40 °C [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…In Figure 4 a, it can be observed that at about −55 °C curvilinear steps were caused by the glass transition of the composites and the curvilinear steps became less distinct with the gradual addition of EUG. This is mainly because at the glass transition temperature, a large number of EUG crystals still existed in the composites owing to the high melting point of the EUG crystalline region, which hindered the molecular chain movement of the composites [ 29 , 30 ]. Besides, it can be found in Table 2 and Figure 4 that with the increase of EUG content, the crystallinity of various MPU/EUG composites gradually increased and their crystallization melting peak gradual appeared and became more and more obvious at about 40 °C [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…where f is the weight fraction of PBS in the blends; ΔH m and ΔH cc are the melting enthalpy and the cold crystallization enthalpy of various PBS samples, respectively; ΔH 0 m is the melting enthalpy of pure PBS that 100% crystallized and its value considered to be 200 J g À1 . [31] The crystalline morphology was observed by POM (Nikon E600, Japan) with a heating platform. The sample was rapidly heated to 220 C and held constant temperature for 5 min to eliminate thermal history.…”
Section: Methodsmentioning
confidence: 99%
“…Seen from Figure 6a, in consequence of the linear molecular chain structure and relatively poor melt viscoelasticity, neat PBS displayed seriously ruptured and coalescent pores during the foaming process, giving oval and irregular cellular sections. [48] Inclusion of CNTs in the PBS matrix caused an enhancement in the melt strength and elasticity, the materials could support cell growth, the pore rupture and combination were reduced, regular and uniform cellular morphology could be founded in their SEM images. [49] On the basis of the cell growth dynamic, the balance between deformability and the strength of polymers played a critical role in the formation of cell structure.…”
Section: Chemphyschemmentioning
confidence: 99%
“…Moreover, Figure 7 showed that in comparison with that of neat PBS foam, the pore size distribution of PBS/CNTs ChemPhysChem nanocomposite foams became narrower for reasons that improved melt strength and viscoelasticity, which also inhibited cell growth. [48] In Table 3, neat PBS foam's cell size and cell density could not be calculated and reported for its irregularity. With the increase of CNTs concentration from 0.5 to 4 wt %, the pore size of different PBS foams reduced from 22.8 to 10.6 μm and their cell density elevated from 1.14 × 10 8 to 6.67 × 10 8 cells/cm 3 , which could be ascribed to two reasons: enhanced melt viscoelastic and the CNTs's heterogeneous nucleation effect.…”
Section: Chemphyschemmentioning
confidence: 99%